Predictive factors for recovery in idiopathic sudden sensory neural hearing loss - Mohamed A. Alhussaini; Suhaib Abdelzaker Mohamed; Mohamad Azzam Abd El-Razek; Enass Sayed Mohamed; Mohamed Omar A. Gad (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Idiopathic sudden sensorineural hearing loss (ISSNHL) is considered a clinical symptom of various conditions. Circulatory disorders, viral infection, labyrinthine membrane rupture, and autoimmune reactions are considered as the common causes, but the exact cause remains unestablished. Various drugs and methods have been used empirically for the treatment of ISSHL. The current study aimed at evaluation factors contributing to the success of standardized medical therapy in cases of ISSNHL. Methods In period between 2019 and 2021, a total 40 patients with ISSNHL were enrolled. All patients were subjected to history taking, physical and ENT evaluation. Patients were managed according to the recent guidelines for managing ISSNHL included systemic steroid and salvage therapy. Results Mean age of studied patients was 42.55 ± 13.14 years with range between 19 and 70 years. Out of the studied patients; 26 (65%) patients were males and 14 (35%) patients were females. Majority (80%) of patients had no comorbidities. Based on the current study, we found that only 12 (30%) patients were improved while 28 (70%) patients were not improved. It was found that majority (58.3%) of improved patients was females. Frequency of vertigo was significantly higher among patients who were not improved. Three (10.7%) patients of not-improved group and 5 (41.7%) patients of improved group had low lymphocyte:monocytes ratio. Conclusion Patients with ISSNHL, the presence of vertigo and late onset of presentation may carry a risk for poor prognosis. Multiple centers studies with large number of patients are warranted to confirm such findings.